Dermatitis Herpetiformis: From the Genetics to the Development of Skin Lesions. (7th June 2012) - Bonciani, Diletta; Verdelli, Alice; Bonciolini, Veronica; D'Errico, Antonietta; Antiga, Emiliano; Fabbri, Paolo; Caproni, Marzia
Abstract : Dermatitis herpetiformis (DH) is a rare autoimmune disease linked to gluten sensitivity with a chronic-relapsing course. It is currently considered to be the specific cutaneous manifestation of celiac disease (CD). Both conditions are mediated by the IgA class of autoantibodies, and the diagnosis of DH is dependent on the detection of granular deposits of IgA in the skin. There is an underlying genetic predisposition to the development of DH, but environmental factors are also important. This paper describes these different factors and discusses the known mechanism that lead to the development of skin lesions.